ANALYSIS WACANA PENGGUNAAN GAYA BAHASA DALAM LIRIK LAGU-LAGU UNGU: KAJIAN STILISTIKA - Imam Mahdil Umami (Dinamika Bahasa dan Budaya, 2009)
This article explores the styles as used in Ungu’s lyrics of several love songs. This is a discourse analysis since the writer views each song within a particular discourse. Unlike other types of discourse analysis, this article employs analytical framework from the point of view of styles. Thus it can be said that this is the study of styles in order to identify and classify for the listeners to further understand the songs. Key words: discourse analysis, styles, stylistics, lyrics